Correction: Effects of service dogs on children with ASD's symptoms and parents' well-being: On the importance of considering those effects with a more systemic perspective. - PLOS ONE Staff (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0295702.].